2017
DOI: 10.1093/mnras/stx967
|View full text |Cite
|
Sign up to set email alerts
|

General relativistic study of astrophysical jets with internal shocks

Abstract: We explore the possibility of formation of steady internal shocks in jets around black holes. We consider a fluid described by a relativistic equation of state, flowing about the axis of symmetry (θ = 0) in a Schwarzschild metric. We use two models for the jet geometry, (i) a conical geometry and (ii) a geometry with non-conical cross-section. Jet with conical geometry is smooth flow.While the jet with non-conical cross section undergoes multiple sonic point and even standing shock. The jet shock becomes stron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…Independently, we notice that Chakrabarti (1999), Chattopadhyay & Kumar (2016), Kumar & Chattopadhyay (2017), and Vyas & Chattopadhyay (2017) have also invoked a jet launching point in the vicinity of a shock. From our own study of particle acceleration, the acceleration is strongest at the shock location, and therefore, should produce the strongest outflows at that point.…”
Section: Introductionmentioning
confidence: 67%
“…Independently, we notice that Chakrabarti (1999), Chattopadhyay & Kumar (2016), Kumar & Chattopadhyay (2017), and Vyas & Chattopadhyay (2017) have also invoked a jet launching point in the vicinity of a shock. From our own study of particle acceleration, the acceleration is strongest at the shock location, and therefore, should produce the strongest outflows at that point.…”
Section: Introductionmentioning
confidence: 67%
“…We propose that the additional powerlaw component originated from the jet. The presence of shock close to base of the jet (Vyas & Chattopadhyay 2017) may produce non-thermal electrons. We checked if the same can be produced due to synchrotron emission from non-thermal electrons at the base of the jet.…”
Section: Modelling the 2003 Outburstmentioning
confidence: 99%
“…If we consider a purely ideal flow, then at the base of the jet the three-velocity should be zero. The Bernoulli parameter which in Schwarzschild metric is E = hγ(1 − 2/r) [20], where h is the specific enthalpy, γ the total Lorentz factor and r the radial coordinate. At the jet base, it becomes E = h b (1 − 2/r b ), as γ b ≈ 1.…”
Section: Radiatively Driven Jetsmentioning
confidence: 99%
“…Here τ is a function of of the jet composition and is defined as τ = 2 − ξ + ξ /η. The methodology to solve equations (2.2-2.5) has been laid down in a series of papers [19,20,18,21]. Assuming the Thomson scattering cross-section i. e., when χ c = 1, we showed that relativistic terminal speeds could be achieved but the temperature of the jet at the base was found to be very high [19,18].…”
Section: )mentioning
confidence: 99%